Carbon reserve in livestock herds and its socioeconomic environmental relationship in the lower basin of the river Shanusi Alto Amazonas -Loreto-Peru - Mathios Flores, Marco (2019)
The carbon reserve in livestock herds is evaluated and its socioeconomic and environmental relationshipin the lower basin of the river Shanusi Alto Amazonas -Loreto-Peru. For the evaluation of carbonreserves, the allometric equations of theManual Determination of Total Carbon Reserves were usedin the dierent systems of land use in Peru and for the characterization of the socioeconomic and environmentalrelationships of the herds of cattle, questionnaire for on-site interviews. The maximum accumulationof carbon per herd of cattlewas 10, 07 tCO2(e)/ha and the minimum of 0, 966tCO2(e)/haat an average of 3, 66 t CO2(e)/ha, out of the 374 hectares that make up the total area of the 20 cattleherds. The simulation of carbon accumulation in 10 years at 5tCO2(e) was of 44556, 82 for the highestand the lowest of $ 21, 39. In the degree of environmental importance 60 % clean air is given, as wellas the range of pasture; in the social part, the family is considered 65 %, motivation for livestock 45 %;In the economic area, 60 % consider it important to dedicate themselves to the cattle herd and obtainother products, as well as to negotiate 60 % carbon credits. The accumulation of carbon in livestockherds is very low because there is no adequate technology in biomass production in improved pastures.In addition, comparisons of systems with improved pastures with trees of native species shouldbe made